Vegetative and floral parameters of African marigold (Tagetes erecta L.) influenced by fertilizer, organic manure and liquid consortia under the semi-arid region of Bundelkhand, Uttar Pradesh, India - Ajay, K; Amit, K; Ajay, K S; Rakesh, K; Kumari, A; Satya, P R; Khushboo, V (Plant Science Today, 2026)
The field experiment was carried out to evaluate the effect of fertilizers, manures and liquid consortia on vegetative and floral characters in marigold cv. Pusa Narangi Gainda. The experiment was conducted at Research Farm, Department of Floriculture and Landscape Architecture, College of Horticulture, Banda University of Agriculture and Technology, Banda during September 2021 to January 2022. The experiment was laid out in Randomized Block Design (RBD) comprising of 10 treatments. Application of 75 % Recommended Dose of Fertilizer (RDF) + vermicompost @ 10 t/ha + liquid consortia @ 625 mL/ha was most effective in increasing the vegetative parameter such as maximum number of primary branches (25.4), maximum number of leaves per plant (258.1), maximum plant spread (41.7 cm), leaf area (45.3 cm2). Further, the treatment also performed better for floral parameters such as first bud initiation (36.2 days), days to first flowering (45.7 days), duration of flowering (61.1 days), number of flowers per plant (34.2), flower yield per plant (0.295 kg) and flowers weight per plot (5.928 kg). Whereas maximum plant height (75.62 cm), stem diameter (12.25 mm), flower diameter (6.1 cm) and flower weight (l.177 g) were recorded in the treatment applied with 75 % RDF + Farmyard Manure (FYM) @ 20 t/ha + liquid consortia 625 mL/ha.